Do Chinese Infrastructure Loans Promote Entrepreneurship in African Countries? - Jonathan Munemo (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
As Chinese loans to Africa have been on an upward trajectory for more than a decade, there are questions about the economic consequences that large scale borrowing from China has on African economies. Jonathan Munemo investigates the impact these rising loans have on entrepreneurship and finds that African countries with a higher percentage of economic infrastructure loans have greater entrepreneurship in the form of new business startups.
Keywords: 330